BRANDING PERBANKAN SYARIAH MELALUI PRODUK-PRODUK PENDANAAN - Tiara Juliana Jaya (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2020)
Sharia banking is expected to apply sharia values to its transactions. Sharia values have a transparent nature. Sharia banking should be based on sharia principles. Referring to sharia principles as described in the Qur'an. Based on the problem then the author took the theme of Sharia banking branding through funding products. The fund-raising consists of three sharia Giro products, sharia savings and sharia deposits. The methods used are methods of analysis used are qualitative methods, and case studies. The triangulation approach of the two techniques of Denzin triangulation (XXX) is the use of sources and methods. It can be used as a cornerstone that by using Sharia bank products has many benefits that can be made for Shahibul Maal (Fund owners) continue to improve performance by using Sharia banking branding on all products especially in funding products. Islamic brand must show and have the appeal to consumers, and provide training and evaluation of human resources in sharia banking that is spearheading to provide vast information to prospective mudharib.